1999
DOI: 10.1103/physrevlett.82.972
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Pairing on the C-Alloyed Si(001) Surface

Abstract: The initial stages of carbon alloying into the Si(001) surface are studied by scanning tunneling microscopy (STM) and density functional theory. Carbon increases the surface roughness compared to the clean surface and induces a c͑4 3 4͒ reconstruction. To explain experimental observations, we propose a novel surface reconstruction model that involves pairing of Si dimers mediated by the presence of a complex of a C dimer and four nearest neighbor subsurface C atoms. The model is backed by total energy and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 14 publications
6
43
0
Order By: Relevance
“…From our first-principles calculations, we found that the geometrical features of the Si-Si dimers in all 12 cells are essentially the same. Surface C is invisible, or shows up as a missing Si atom, in STM experiments [16]. This implies that one cannot distinguish, using standard microscopy, between pure Si(100) or Si(100) with vacancies, and a configuration with C in the third layer; the only criterion is the long-range order and the change of the reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From our first-principles calculations, we found that the geometrical features of the Si-Si dimers in all 12 cells are essentially the same. Surface C is invisible, or shows up as a missing Si atom, in STM experiments [16]. This implies that one cannot distinguish, using standard microscopy, between pure Si(100) or Si(100) with vacancies, and a configuration with C in the third layer; the only criterion is the long-range order and the change of the reconstruction.…”
mentioning
confidence: 99%
“…Guided by previous work, [2,12,13,16] we can establish a set of rules which should be obeyed by low energy configurations of the CSi(100) system, namely:…”
mentioning
confidence: 99%
“…This was reproduced by Sakamoto et al, 2 and later Müller et al 3 reported that this reconstruction also appeared when a clean Si͑100͒ surface was annealed in vacuum. It turns out that this reconstruction has been formed with a wealth of methods; Si deposition, 1,2,4,5 C deposition, [6][7][8][9][10][11] Ge deposition, 12 H exposure, [13][14][15][16][17][18][19] C 2 H 4 and C 2 H 2 treatment, 20-24 SiH 4 /Si 2 H 6 growth, [25][26][27][28][29] annealing in vacuum, 3,[30][31][32][33][34][35][36] B deposition, [37][38][39] and O or S treatment. [40][41][42] Several models for the reconstruction have been proposed: Pandey's -bonded defect model, 30,43 missing dimer, 9,13 parallel ad-dimer, 15 and mixed ad-dimer 15 models, and it has been debated whether it is a pure Si reconstruction or if it contains any foreign species.…”
Section: Introductionmentioning
confidence: 99%
“…There were some Auger electron spectroscopy ͑AES͒ investigations reporting a clean surface 27,30,42 while others reported traces of C present on the surface. 13,6 In recent years most investigations seem to support the idea that the reconstruction is C related [7][8][9]19,22,24 and there have been some attempts to estimate the carbon concentration. 6,7,9,20,22 Some have argued for reconstruction models containing an integer number of C atoms per unit cell while others claim that subsurface C and/or surface C produces the reconstruction indirectly-by strain or otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage carbonization of a Si(100) surface, 2 × n (6 ≤ n ≤ 12) [27,28] and c(4 × 4) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] reconstructions have been reported. However, similar 2 × n [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and c(4 × 4) reconstructions have been reported without carbonization.…”
Section: Introductionmentioning
confidence: 99%